2020
DOI: 10.1007/s10103-020-03141-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of photobiomodulation therapy to accelerate bone formation in the mid palatal suture after rapid palatal expansion: a randomized clinical trial

Abstract: To evaluate the efficiency of photobiomodulation therapy (PBMT) in the midpalatal suture (MPS) and pain sensation in patients undergoing rapid palatal expansion (RPE). Thirty-four individuals with the diagnosis of skeletal maxillary hypoplasia were divided in two groups: laser (n = 18) and control (n = 16). Treatment plan consisted of the use of the Hyrax expander in all patients. Subjects in the laser group were irradiated with diode laser (980 nm, 0.3 W) in six spots bilaterally distributed along the MPS for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…In Matos and colleagues' study, 13 unlike the other three, the mean age of the control group (8.2 years) was significantly lower than the laser group (9.2) (P = 0.0308), but sex was kept similar between the two groups. This article showed no significant difference in bone formation and pain sensation in the case of laser irradiation.…”
Section: Lllt Accelerates Bone Repair After Rmementioning
confidence: 75%
See 4 more Smart Citations
“…In Matos and colleagues' study, 13 unlike the other three, the mean age of the control group (8.2 years) was significantly lower than the laser group (9.2) (P = 0.0308), but sex was kept similar between the two groups. This article showed no significant difference in bone formation and pain sensation in the case of laser irradiation.…”
Section: Lllt Accelerates Bone Repair After Rmementioning
confidence: 75%
“…A third author evaluated any disagreements to reach a solution. Finally, 4 articles 12,13,25,26 met the inclusion criteria. The PRISMA diagram of the included studies is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations